Gclc deficiency in mouse CNS causes mitochondrial damage and neurodegeneration. (31st January 2017) - Feng, Weiyi; Rosca, Mariana; Fan, Yuxuan; Hu, Yufen; Feng, Pingfu; Lee, Hyoung-Gon; Monnier, Vincent M.; Fan, Xingjun
Abstract: Gamma glutamyl cysteine ligase (GCL) is the rate-limiting enzyme for intracellular glutathione (GSH) synthesis. The GSH concentration and GCL activity are declining with age in the central nervous system (CNS), and is accompanied by elevated reactive oxygen species (ROS). To study the biological effects of low GSH levels, we disrupted its synthesis both at birth by breeding a Gclc loxP mouse with a thy1-cre mouse (NEGSKO mouse) and at a later age by breeding with a CaMKII-ERT2-Cre (FIGSKO mouse). NEGSKO mice with deficiency of the Gclc in their entire CNS neuronal cells develop at 4 weeks: progressive motor neuron loss, gait problems, muscle denervation and atrophy, paralysis, and have diminished life expectancy. The observed neurodegeneration in Gclc deficiency is of more chronic rather than acute nature as demonstrated by Gclc targeted single-neuron labeling from the inducible Cre-mediated knockout (SLICK) mice. FIGSKO mice with inducible Gclc deficiency in the forebrain at 23 weeks after tamoxifen induction demonstrate profound brain atrophy, elevated astrogliosis and neurodegeneration, particularly in the hippocampus region. FIGSKO mice also develop cognitive abnormalities, i.e. learning impairment and nesting behaviors based on passive avoidance, T-Maze, and nesting behavior tests. Mechanistic studies show that impaired mitochondrial glutathione homeostasis and subsequent mitochondrial dysfunction are responsible for neuronal cell loss. This was confirmed by mitochondrial electron transporter chain activity analysis and transmission electron microscopy that demonstrate remarkable impairment of state 3 respiratory activity, impaired complex IV function, and mitochondrial swollen morphology in the hippocampus and cerebral cortex. These mouse genetic tools of oxidative stress open new insights into potential pharmacological control of apoptotic signaling pathways triggered by mitochondrial dysfunction.